ASSESSING QUALITY OF LIFE AFTER LAPAROSCOPIC CHOLECYSTECTOMY IN SAUDI ARABIA AND THE EFFECT OF LOW-FAT DIET: A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
Background: Evaluation of quality of life, patient satisfaction, and postoperative recovery are essential for determining if the surgery was successful in terms of the future health of the patient. The purpose of this study is to evaluate the quality of life and effect of diet modifications among patients who had laparoscopic cholecystectomy in Saudi Arabia.Methodology: From July to November 2024, a cross-sectional study was carried out with a focus on patients in Saudi Arabia who had received LC for gallstone disease. We used a comprehensive questionnaire that included both closed- and open-ended questions to provide a comprehensive understanding to assess patient happiness, quality of life, and the perceived value of LC. Some questions were added to assess the effect of a low-fat diet postoperatively.Results: The study involved 409 participants. Overall, about 76.8% felt satisfied with the care they received and reported positive experiences. However, a significant number, 50.1%, did encounter complications during their recovery. 9.7% of the participants observed improvements in their quality of life after the surgery, although nearly 40% (39.6%) reported that the pain they experienced was greater than they had expected. Many participants felt that the information provided before the surgery could have been better.Conclusion: Although satisfaction rates are very high, attention should also be paid for taking account of the complications and adverse effects reported by participants. Longitudinal QoL outcomes from this surgical cohort along with diverse demographic and regional variables in identification of determining recovery factors need to be studied to improve patient care.Education is needed for better outcomes and better healthcare experience in this population, especially about dietary management post-surgery.